Two-Dimensional Modeling of Silicon Nanowires Radial Core-Shell Solar Cells. (24th May 2018) - Zeng, Qiang; Meng, Na; Ma, Yulong; Gu, Han; Zhang, Jing; Wei, Qingzhu; Kuang, Yawei; Yang, Xifeng; Liu, Yushen
Abstract : Silicon nanowires radial core-shell solar cells have recently attracted significant attention as promising candidates for low cost photovoltaic application, benefit from its strong light trapping, and short radial carrier collection distances. In order to establish optics and electricity improvement, a two-dimensional model based on Shockley-Read-Hall recombination modes has been carried out for radial core-shell junction nanowires solar cell combined with guided resonance modes of light absorption. The impact of SiNWs diameter and absorption layer thickness on device electrical performance based on a fixed nanowires height and diameter-over-periodicity were investigated under illumination. The variation in quantum efficiency indicated that the performance is limited by the mismatch between light absorption and carriers' collection length.